TOD typologies for metro stations based on the butterfly model - Wu, Tao; Yuan, Zhen; Gao, Linna; Zhang, Mengying; Li, Mingjing (Frontiers in Environmental Science, 2024)
As a promising planning strategy for urban sustainability, transit-oriented development (TOD) has been widely encouraged and adopted to integrate land use and transport systems. Because of the different applications in form, function and impact, it is necessary to explore context-based TOD typologies to better map the TOD specificities and focus on strategic planning. As the best-known method, the node-place model provides a useful analytical framework to evaluate TOD typologies. However, by using two indexes to aggregate the node and place value, details of some important TOD characteristics are disregarded in this model. Proposing a multi-axial indexes system, the butterfly model can perform a more detailed evaluation of node and place. In this research, we have revised and optimized the butterfly model and taken Tianjin Metro Line 1 as a case study. We find that all stations can be divided into five TOD types with significant spatial variations. TOD principles have already been implemented in Tianjin with good integration between metro system and land use. The method demonstrated in this paper equips urban planners with a useful tool for evaluating TOD performance and adopting more targeted strategies.